Presentation of Ocular and Orbital Dermoid Cysts at Holy Family Hospital Rawalpindi - Ali Raza, Sana Nadeem (Pakistan Journal of Ophthalmology, 2012)
Purpose: To evaluate the presentation of dermoid cysts related to the eye and orbit, appropriate management and results. Material & Methods: This prospective study was conducted in Department of Ophthalmology, Holy Family Hospital, Rawalpindi. A total of twenty eight (28) cases of dermoids presented to us from 1st January, 2007 to 1st December, 2011. CT scanning/MRI were done where deemed necessary and all lesions were confirmed on histopathology. Limbal dermoids were shaved off with conjunctival autografting or flap. Superficial dermoids were removed via appropriate skin incisions and for deep dermoids, we performed orbitotomies. Results: Out of 28 cases of dermoids, 12 were limbal dermoids, 5 were superficial superonasal dermoids and 2 were superficial superotemporal, and 9 were deep orbital dermoid cysts. One superficial dermoid presented as a recurrence. Post-operative hematoma developed in one patient only. Follow up ranged from one month to four years. Conclusion: Dermoid cyst en bloc excision is a relatively safe procedure with minimal complications. Recurrence can be effectively prevented by a careful evaluation and complete surgical removal.